2003
DOI: 10.1348/000712603767876299
|View full text |Cite
|
Sign up to set email alerts
|

Word frequency effect on repetition priming as a function of prime duration and delay between the prime and the target

Abstract: Two experiments studied the necessary conditions for the occurrence of repetition priming and word frequency effect on priming in a lexical decision task. To examine the role of prime processing duration, the prime was presented either for 50 ms or for 700 ms, and an interfering task was introduced between the prime and the target in order to restrict the time during which the prime was effectively processed and to limit it to exactly 50 ms or 700 ms. The interstimulus interval (ISI) between the prime and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 59 publications
1
31
0
Order By: Relevance
“…And, by the Bayesian Reader account, masked priming should be limited to adjacent prime-target pairings that become conflated in the act of perception. Consistent with the latter accounts, initial tests suggested that masked priming was limited to a single trial and could be detected after no more than a second or two between prime and target presentations (e.g., Ferrand, 1996;Forster, Booker, Schacter, & Davis, 1990;Forster & Davis, 1984;Greenwald et al, 1996;Humphreys, Besner, & Quinlan, 1988;Versace & Nevers, 2003). In contrast, priming effects with unmasked stimuli can be very long lasting (e.g., Kolers, 1976).…”
Section: Duration Of Masked Primingmentioning
confidence: 79%
“…And, by the Bayesian Reader account, masked priming should be limited to adjacent prime-target pairings that become conflated in the act of perception. Consistent with the latter accounts, initial tests suggested that masked priming was limited to a single trial and could be detected after no more than a second or two between prime and target presentations (e.g., Ferrand, 1996;Forster, Booker, Schacter, & Davis, 1990;Forster & Davis, 1984;Greenwald et al, 1996;Humphreys, Besner, & Quinlan, 1988;Versace & Nevers, 2003). In contrast, priming effects with unmasked stimuli can be very long lasting (e.g., Kolers, 1976).…”
Section: Duration Of Masked Primingmentioning
confidence: 79%
“…) or phonologically (Goldinger et al 1992;etc. ) related, or by repetition (Versace and Nevers 2003;etc.). On the other hand, a word is inhibited (i.e.…”
Section: 3mentioning
confidence: 96%
“…As such, it is difficult to definitively rule out the possibility that the stimulus quality × repetition priming interaction partly reflects episodic memory traces, which are outside the scope of computational word recognition models (Blais et al, 2011). For example, in Forster andDavis' (1984) lexical decision study, the effects of repetition priming and word-frequency were additive with masked primes and overadditive with unmasked primes (see also Versace & Nevers, 2003), suggesting that the interaction reflected the influence of the prime's episodic trace. To shed more light on this issue, future research might explore whether the intriguing interaction between stimulus quality and repetition priming holds up when masked primes are used.…”
Section: Semantic Richness Effects: the Role Of Feedbackmentioning
confidence: 97%